1995
DOI: 10.1159/000098890
|View full text |Cite
|
Sign up to set email alerts
|

Thalamotomy for Essential and Cerebellar Tremor

Abstract: Thalamotomy significantly suppressed essential tremor in 86% of patients and restored the ability to hold a glass to drink in 81% in the long term, but tremor recurred in 5/21 patients up to 5 years postoperatively, unlike parkinsonian patients whose tremor seldom recurs after 3 months. In multiple sclerosis (MS), 67% of those followed showed sustained significant suppression of tremor, 67% sustained improvement in dexterity, 50% in drinking; tremor recurred up to 5 years postoperatively. In other cerebellar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 0 publications
2
51
0
1
Order By: Relevance
“…This rate is higher than the rates in most published series; for example, the rate of permanent complications ranged from 9 to 23 percent in patients with Parkinson's disease, 1,6 13 to 38 percent in patients with essential tremor, 5,8 and 16 to 41 percent in patients with multiple sclerosis. 7,9 However, surgical studies that included prospective collection of data reported considerably higher rates of adverse events than retrospective studies. 41,42 In our study, the use of microelectrode recordings to identify the optimal location for the intervention may have reduced morbidity, although this issue is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…This rate is higher than the rates in most published series; for example, the rate of permanent complications ranged from 9 to 23 percent in patients with Parkinson's disease, 1,6 13 to 38 percent in patients with essential tremor, 5,8 and 16 to 41 percent in patients with multiple sclerosis. 7,9 However, surgical studies that included prospective collection of data reported considerably higher rates of adverse events than retrospective studies. 41,42 In our study, the use of microelectrode recordings to identify the optimal location for the intervention may have reduced morbidity, although this issue is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of Vim thalamic stimulation over thalamotomy include potential reversibility, reduced morbidity with bilateral procedures, and the dynamic nature of the treatment allowing adjustment and fine tuning of the device for optimal function [15]. The relative benefit of this procedure over thalamotomy will ultimately depend on the relative cost and long-term morbidities, such as frequency of battery replacement, hardware failures, and infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although ET occurs more frequently than Parkinson's disease, the number of patients referred for surgery is relatively small. Only a few studies have focused on surgical treatment of ET, and long-term results of stereotactic VIM thalamotomy in patients with ET are not well represented in the literature [5][6][7][8][9]. We have summarized our experience with stereotactic VIM thalamotomy for treatment of medically intractable ET and present here our results from a series of 43 thalamotomies performed in 37 patients.…”
mentioning
confidence: 99%